Compact low-repetition-rate femtosecond optical parametric oscillators enabled by Herriott cells - Allan, Ewan; Bajek, David; McCracken, Richard A. (Optics express, 2024)
We report the design and characterization of a femtosecond optical parametric oscillator containing an intracavity Herriott cell. Pumped by a 49.16-MHz Yb:fiber laser, the signal wavelength could be tuned over 1440-1530 nm, with the Herriott cell containing 81% of the free-space cavity length required for synchronous operation. We also report a 12.29-MHz OPO using a sub-harmonic pumping approach, extending the Herriott cell OPO concept to low-repetition-rate cavities.